30.2k views
0 votes
Hiiii....plzzz help me....​

Hiiii....plzzz help me....​-example-1
User Inwit
by
5.2k points

2 Answers

0 votes

Answer:

yess

Explanation:

User Cjm
by
6.2k points
3 votes

Explanation:

tan(π/8)

Using half angle formula:

tan(θ/2) = (1 − cos θ) / sin θ

tan(π/8) = (1 − cos(π/4)) / sin(π/4)

= (1 − √2/2) / (√2/2)

= (2 − √2) / √2

= (2√2 − 2) / 2

= √2 − 1

If you want to prove it using the formula you derived, use A = π/8.

2A + B = π/4

2(π/8) + B = π/4

B = 0

Therefore:

tan B = (1 − 2 tan A − tan² A) / (1 + 2 tan A − tan² A)

tan 0 = (1 − 2 tan(π/8) − tan²(π/8)) / (1 + 2 tan(π/8) − tan²(π/8))

0 = 1 − 2 tan(π/8) − tan²(π/8)

tan²(π/8) + 2 tan(π/8) − 1 = 0

tan²(π/8) + 2 tan(π/8) + 1 = 2

(tan(π/8) + 1)² = 2

tan(π/8) + 1 = ±√2

tan(π/8) = ±√2 − 1

Since π/8 is in the first quadrant, we know tan(π/8) > 0.

tan(π/8) = √2 − 1

sin 20 sin 40 sin 60 sin 80

sin 60 = √3/2, so:

√3/2 (sin 20 sin 40 sin 80)

We can use product to sum formula to simplify. For the first attempt, let's use the product of the first two terms.

√3/2 (sin 20 sin 40) sin 80

√3/4 (cos(40−20) − cos(40+20)) sin 80

√3/4 (cos 20 − cos 60) sin 80

√3/4 (cos 20 − 1/2) sin 80

√3/8 (2 cos 20 − 1) sin 80

Distribute:

√3/8 (2 cos 20 sin 80 − sin 80)

Repeat product to sum formula:

√3/8 (sin(80+20) + sin(80−20) − sin 80)

√3/8 (sin 100 + sin 60 − sin 80)

√3/8 (sin 100 + √3/2 − sin 80)

√3/8 (sin(180−80) + √3/2 − sin 80)

Use angle difference formula:

√3/8 (sin 180 cos 80 − sin 80 cos 180 + √3/2 − sin 80)

√3/8 (sin 80 + √3/2 − sin 80)

3/16

That's one way. Let's do it another way. This time, we'll use the product of the last two terms.

√3/2 sin 20 (sin 40 sin 80)

Product to sum:

√3/4 sin 20 (cos(80−40) − cos(80+40))

√3/4 sin 20 (cos 40 − cos 120)

√3/4 sin 20 (cos 40 + 1/2)

√3/8 sin 20 (2 cos 40 + 1)

Distribute:

√3/8 (2 cos 40 sin 20 + sin 20)

Repeat product to sum:

√3/8 (sin(40+20) − sin(40−20) + sin 20)

√3/8 (sin 60 − sin 20 + sin 20)

√3/8 sin 60

√3/8 (√3/2)

3/16

User Shen
by
6.4k points